Faculty of Mechanical Engineering - Peter Zvolensky (Communications - Scientific letters of the University of Zilina, 2003)
The Faculty of Mechanical Engineering, University of Žilina, carries out its activities in the environment of other Slovak faculties based on mechanical and production engineering.The Faculty deals with standard disciplines (such as measurement, automation, industrial engineering, technological engineering, mechanic and strength, design and machine elements) and with specific engineering disciplines (such as machinery maintenance engineering; railway vehicles; engines and lifting equipment; heat and hydraulic machines). The specific engineering disciplines are unique for Slovak faculties. Transport technology and transport engineering are characteristic for the Faculty.